2022
DOI: 10.14742/ajet.7695
|View full text |Cite
|
Sign up to set email alerts
|

Research issues of the top 100 cited articles on information literacy in higher education published from 2011 to 2020: A systematic review and co-citation network analysis

Abstract: Information literacy is a core research topic in the field of library and information science. The developmental context of this field can be examined through a long-term retrospective analysis of relevant literature. This study explored the research trends and potential research issues in the top 100 most frequently cited articles on information literacy in higher education published from 2011 to 2020. In addition to a systematic review, this study employed bibliometric methods, including co-citation network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 57 publications
1
31
0
1
Order By: Relevance
“…. In line with this data, a previous study that analyzed the most cited articles found that the eld of engineering was one of the most proli c (H. Chu et al, 2023). However, the eld of Arts and Humanities had the highest impact according to the global average.…”
Section: )supporting
confidence: 61%
“…. In line with this data, a previous study that analyzed the most cited articles found that the eld of engineering was one of the most proli c (H. Chu et al, 2023). However, the eld of Arts and Humanities had the highest impact according to the global average.…”
Section: )supporting
confidence: 61%
“…The United States had the highest number of publications, and the most cited articles were about implementing virtual tutoring to improve learning. Chu et. al.…”
Section: Extant Systematic Reviewsmentioning
confidence: 99%
“…The purpose of this study is in response to the appeal from scholars (viz., Chu et al, 2022;Hinojo-Lucena et al, 2019;Zawacki-Richter et al, 2019) to research to investigate the benefits and challenges of AIEd within HE settings. As the academic knowledge of AIEd HE…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the chronological limitations established seemingly go somewhat against the grain (Macaro, 2019), in light of the most ground-breaking recent developments within the field of GenAI that have taken place since 2022, marked by the launch of GPT 3.5 until the time of writing, this time period has been selected to focus on studies which specifically address these through the lens of EMI HE. Such an investigation in a distinct field or even into a different phenomenon may, in fact, seem to be implausible or perhaps redundant, given that international cognate studies from recent years have previously delved into this area of investigation (e.g., Chen et al, 2020;Chu et al, 2022;González-Calatayud et al, 2021;Ouyang et al, 2022;Zawacki-Richter et al, 2019). Nonetheless, even the most recent scholarly example has a scope which predates the monumental, rapid, and prolific singular developments in GenAI and HE that have occurred most recently.…”
Section: Introductionmentioning
confidence: 99%